#INDONESIAGELAP DI PLATFORM X: Perwakilan Perlawanan Masyarakat Madani Melalui Aktivisme Hashtag - Gladys Intan Juniarta; Anabelle Graciani Nathaniel Sirait; Muradi (Halu Oleo University, 2025)
#IndonesiaGelap on Platform X, which emerged on February 17, 2025, with over 81,900 posts, is interpreted as a representation of civil society resistance and digital activism in contemporary Indonesia. This qualitative study uses literature review methods to explore how social media has become a primary public space for voicing aspirations and criticism of government policies, particularly approval of the revision of the Indonesian National Armed Forces Law and other issues, such as education budget cuts. The word